Adobe buildings damaged during KovancA±lar (ElazA±AY) earthquake on March 8, 2010 and their earthquake resistances - Sunkar, Murat; Aksoy, H. Suha (Korean Society of Civil Engineers-Ksce, 2015)
This study is intended to determine the resistance and strength of adobe samples taken from buildings damaged and collapsed during an earthquake that hit the east of KovancA +/- lar district (ElazA +/- AY province) on March 8, 2010. This earthquake, which struck 30-35 km east of KovancA +/- lar district, with a magnitude of 6.0, affected more than 30.000 people and resulted in 42 deaths. The greatest damage and destruction caused by this earthquake were to stone, adobe and stone-adobe buildings. The compressive strength, granulometry, soil class and straw rate of samples taken from severely damaged BayramyazA +/-, Ok double dagger ular, Tabanozu and YalnA +/- z double dagger am villages were determined in order to find out the earthquake resistance of adobe buildings. As a result of analyses, samples with low rate of clay and straw were revealed to be low strength, whereas those with high rate of such materials were shown to be high strength. Consequently, it was seen that the earthquake resistance of adobe buildings depends on the characteristics of construction material.
Keywords: kovancilar earthquake; adobe; compressive strength; soil class